REDUKSI NILAI AKTIF MATERIAL GUNUNG DENGAN STABILISASI PADA TIMBUNAN PILIHAN PERKERASAN PERBUTIRAN JALAN RAYA - Gon, Kasmir (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2024)
The use of selected embankment materials in highway pavement work must meet the technical requirements in accordance with the applicable specifications. One source of mountain material exploited by the general public to meet the needs of residential construction and contractors on government projects is Golo Lalong Village, East Manggarai Regency, NTT Province. From previous research it is known that the mountain material from the quarry is not suitable for selected embankment work on roads because its active value is > 1.25 which is categorized as active material. This research was carried out with the aim of stabilizing the mountain material of Golo Lalong Village with mountain material from Kisol to reduce its active value. With 15% stabilization of Ex Kisol mountain material it is able to reduce the plastic limit value from 9 to 13 to 3 and the percentage passing the Number 200 sieve varies from 5.16% to 6.87%. The active value of the material resulting from the stabilization was reduced significantly from 1.25 to 2.43 become 0.44 to 0.97 so that the Golo Lalong Village mountain material with 15% stabilization of the Ex Kisol mountain material is suitable for use as an embankment option for highway granular pavement.